An alpha-synuclein MRM assay with diagnostic potential for Parkinson’s disease and monitoring disease progression - Yang, Li (Proteomics Clin Appl, 2017)
AIM: The alpha-synuclein (α-syn) level in human cerebrospinal fluid (CSF), as measured by immunoassays, is promising as a Parkinson’s disease (PD) biomarker. However, the levels of total α-syn are inconsistent among studies with large cohorts and different measurement platforms. Total α-syn level also does not correlate with disease severity or progression. Here, we developed a highly sensitive Multiple Reaction Monitoring (MRM) method to measure absolute CSF α-syn peptide concentrations without prior enrichment or fractionation, aiming to discover new candidate biomarkers. RESULTS: Six peptides covering 73% of protein sequence were reliably identified, and two were consistently quantified in cross-sectional and longitudinal cohorts. Absolute concentration of α-syn in human CSF was determined to be 2.1ng/mL. A unique α-syn peptide, TVEGAGSIAAATGFVK (81-96), displayed excellent correlation with previous immunoassay results in two independent PD cohorts (p < 0.001), correlated with disease severity, and its changes significantly tracked the disease progression longitudinally. CONCLUSIONS: An MRM assay to quantify human CSF α-syn was developed and optimized. Sixty clinical samples from cross-sectional and longitudinal PD cohorts were analyzed with this approach. Although further larger-scale validation is needed, the results suggest that α-syn peptide could serve as a promising biomarker in PD diagnosis and progression.